(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The works of the prominent poet Nizami Ganjavi are at the fortfront of the Azerbaijan literary criticism, besides his personality is mentioned as the object of study in works of art many times. In the poetry of Azerbaijan, the depiction of the image of Nizami Ganjavi had manifested itself before the twentieth century. In the nineteenth-century literature, unlike in the medieval poetry, Nizami Ganja was given different characterizations. The medieval writings accentuated the spiritual life of Nizami, his eternal life as a prominent mentor among poets. However, the indifference to the memory of Nizami Ganjavi was first regretfully noted in the nineteenth century in the creativity of Seid Azim Shirvani. In the poetry of the twentieth century the image of Nizami was displayed with dazzling colors and the eternity of the verbal world of the poet was repeatedly mentioned. The most frequent themes encountered in the press and books were references to Nizami as the coryphaeus master, meditations by the poet’s grave, oblivion and his grave destruction, Nizami Ganjavi’s service to national thinking, etc. Even in modern literary process, Nizami’s museum is considered as an artistic image.